Interpreting Declarative Questions in Australian Courts : An Experimental Study of Chinese-English Professional Interpreters in Remote Settings - Yi, Ran (International Journal of Linguistics and Translation Studies, 2023)
In common law courtrooms, questions are not merely questions, as they are often used strategically with varying illocutionary force and point. This article dealt with the under-investigated Chinese-English interpretations of declarative questions in virtual court proceedings. Drawn upon the interpreting performance data collected from 50 certified interpreters, the findings revealed that systematic alterations of declaratives that shift the pragmatic force in cross-examination. Such alterations may have further implications for counsels’ questioning strategies and judicial outcomes. This study intends to inform future pedagogical practice in specialised court interpreter training.